Comparing terrestrial insect diversity using pitfall trap under different agricultural landscapes - Madis, Rexie Meekenddey (2018)
Forest conversion for agricultural expansion is among the major driver of biodiversity losses worldwide. Agricultural land use, however, may have different impacts on overall biodiversity especially insects. Understanding landscape heterogeneity between monoculture and polyculture systems can improve conservation of insect biodiversity in agricultural plantations. The present study compared terrestrial insect abundance and order richness between polyculture orchard, monoculture rubber and monoculture oil palm plantations. The study was carried out in Kampung Sungai Lalah, Pedas, Negeri Sembilan from January to February 2018. Terrestrial insects were sampled using pitfall traps at all agricultural landscapes (total sampling point = 45). In overall, the study recorded 2555 individuals belonging to 10 insect orders. Polyculture orchard recorded greater insect abundance and order richness followed by monoculture oil palm and monoculture rubber plantations. Polyculture orchard also showed greater vegetation cover and relative humidity. In addition, Dermaptera and Homoptera were also recorded in polyculture orchard and monoculture oil palm plantations. The findings from this study indicate that polyculture systems can support greater insect abundance and diversity due to complex vegetation structure and higher humidity. Local diversity of plants and insects also represent improved ecosystem services such as decomposition rates. The findings suggest that agricultural management should prioritize polyculture systems to improve insects conservation and ecosystems services.